WORKSHOP PEMBUATAN MEDIA PEMBELAJARAN BERBASIS DIGITAL BAGI GURU SD INPRES BERTINGKAT OEBA 5 - Bulu, Vera Rosalina; Koroh, Taty Rosiana; Ga, Paulina Riwu; Lehan, Andriyani D.; Fointuna, Daniel Williams; Daki, Sandrianus Wolo; Saleh, Siti Aisyah; Elodea, Fita Febriati (LPPM Institut Pendidikan Nusantara Global, 2024)
Digital learning media creation workshops were conducted at the primary school in Oeba V. The total number of participants in this activity was 31 people. The methods used in dedication to this community are the methods of training and support. Qualitatively obtained results include understanding, skills, and motivation regarding digitization in learning, learning media and its implementation in learning in primary schools, making AKM tests for simulation of AKM using the I Spring Suite application, making teaching materials, quizzes, and interactive games using the Wordwall application, genially, and educaplay. Quantitatively achieved results are: 15 teachers capable of producing AKM tests based on HTML and Android using the Spring Suite application; 1 teacher capable of creating teaching material and interactive games with the application genially; 4 teachers able to create interactive games using wordwall applications, Educaplay